Analysis of Porcine RIG-I Like Receptors Revealed the Positive Regulation of RIG-I and MDA5 by LGP2 - Li, Shuangjie; Yang, Jie; Zhu, Yuanyuan; Wang, Hui; Ji, Xingyu; Luo, Jia; Shao, Qi; Xu, Yulin; Liu, Xueliang; Zheng, Wanglong; Meurens, François; Chen, Nanhua; et al. (Frontiers in Immunology, 2021)
The RIG-I like receptors (RLRs) play critical roles in sensing and fighting viral infections especially RNA virus infections. Despite the extensive studies about RLRs in medicine, there is a lack of systemic investigation of livestock animal RLRs. In this study, we characterized the porcine RLR members RIG-I, MDA5 and LGP2. Compared with their human counterparts, porcine RIG-I and MDA5 exhibited similar signaling activity to distinct dsRNA and viruses, via similar and cooperative recognitions. Porcine LGP2, without signaling activity, was found to positively regulate porcine RIG-I and MDA5 in transfected porcine alveolar macrophages (PAMs), gene knockout PAMs and PK-15 cells. Mechanistically, LGP2 interacts with RIG-I and MDA5 upon cell activation, and promotes the binding of dsRNA ligand by MDA5 as well as RIG-I. Accordingly, porcine LGP2 exerted broad antiviral functions. Intriguingly, we found that porcine LGP2 mutants with defects in ATPase and/or dsRNA binding presents constitutive activity which are likely through RIG-I and MDA5. Our work provided significant insights into porcine innate immunity, species specificity and immune biology.